Multi-stage fluid infiltration and metasomatism in supra-subduction zone mantle: evidence from halogens and noble gases in the Leka Ophiolite Complex, Norway. (15th August 2021) - Carter, Elliot J.; O'Driscoll, Brian; Burgess, Ray; Clay, Patricia L.
Highlights: Volatiles in Leka ophiolite rocks reveal multiple phases of alteration/metasomatism. Leka rocks have very heterogeneous halogen and noble gas compositions. Distinct metasomatic events can be identified and have been preserved for ∼0.5 Gyr. Abstract: Subduction of hydrated oceanic lithosphere represents a profound coupling of the Earth's surface and its interior, with significant implications for both the internal dynamics and chemistry, as well as the surface habitability, of our planet. Serpentinised lithospheric mantle is increasingly recognised as an important component in the geochemical cycling of many volatile species. However, our understanding of the extent of hydration and heterogeneity in volatile geochemistry at depth is limited by a lack of samples from in situ lithospheric mantle. In this study, we apply coupled analyses of halogen abundances and noble gas isotopes to a suite of mineral separates from ultramafic lithologies from the Leka Ophiolite Complex, Norway, in order to trace the sources of fluids and critically assess the relative timing of high- and low-temperature fluid infiltration episodes. Results indicate extreme halogen abundance heterogeneity in the mantle and lower crustal transition zone of the Leka ophiolite, covering much of the known global range of serpentinite compositions. The data extend from near seawater-like compositions (as wt/wt: Br/Cl = 3.47 × 10 −3, I/Cl = 3.04 × 10 −6 ) to very high values of Br/Cl (≤9.9 × 10 −3 ) and I/Cl (≤6.7 × 10 −3 ), and are characterised by a marked decoupling of halogens, both from one another and from the noble gases. Relative enrichments in I, 84 Kr, 132 Xe and radiogenic 40 Ar in serpentinites and fresh minerals are attributed to supra-subduction zone fluid infiltration at high temperature, followed by serpentinisation involving variable mixtures of seawater, and fluid derived from terrigenous sediment and organic-rich sedimentary pore fluid. In addition, alteration by brine or assimilation of brine during hydrothermal circulation has resulted in enrichment of Br in some samples. These enrichments are absent, or much less pronounced, in harzburgite samples suggesting these rocks preserve an earlier episode of seawater dominated serpentinisation within a SSZ setting. Together, these observations allow deconvolution of a series of metasomatic events and indicate that hydration was asynchronous, resulting in low and high temperature events mutually overprinting one another. Although this complicates our understanding of Leka and other ophiolites as straightforward natural laboratories for oceanic serpentinisation, it demonstrates that complex multi-phase volatile histories can be preserved in ophiolitic materials over timescales of at least ∼ 0.5 Gyr. Ophiolites therefore have the potential to be employed as archives of a diverse range of fluid processes operating over multiple temporal and spatial scales during subduction.